2022
DOI: 10.35134/ekobistek.v11i2.318
|View full text |Cite
|
Sign up to set email alerts
|

Dukungan Organisasi, Keadilan Organisasi dan Komitmen Organisasi Terhadap Kinerja Karyawan Pada PT. Batanghari Barisan Padang

Abstract: Human resources are important for the company because they have a role as a potential driver of all company activities. Companies that have quality human resources can easily achieve the performance that has been set. Performance measurement is a very important thing as a whole in an organization. Every company will always try to improve employee performance for the company's success. Several factors that can affect employee performance include: organizational support, organizational justice, and organizationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 12 publications
3
5
0
3
Order By: Relevance
“…Organizational support is the degree to which employees believe the organization values their contributions and cares about their well-being (Robbins & Judge, 2018). This is in line with the research by Diah & Nugraheni (2021), Irianti & Bernarto (2021), Ningrum & Agung (2021), Arifin & Darmawan (2022), and Karlinda et al, (2022) which found that organizational support has a significant positive effect on employee performance, however, this is different from the research of Tombokan et al, (2019), andFitriani et al, (2022) who found organizational support to have a positive but not significant effect on employee performance.…”
Section: Introductionsupporting
confidence: 84%
See 2 more Smart Citations
“…Organizational support is the degree to which employees believe the organization values their contributions and cares about their well-being (Robbins & Judge, 2018). This is in line with the research by Diah & Nugraheni (2021), Irianti & Bernarto (2021), Ningrum & Agung (2021), Arifin & Darmawan (2022), and Karlinda et al, (2022) which found that organizational support has a significant positive effect on employee performance, however, this is different from the research of Tombokan et al, (2019), andFitriani et al, (2022) who found organizational support to have a positive but not significant effect on employee performance.…”
Section: Introductionsupporting
confidence: 84%
“…The research results of Diah & Nugraheni (2021), Irianti & Bernarto (2021) Ningrum & Agung (2021) suggest that higher organizational support will have a positive effect on improving employee performance. This is reinforced by the research results of Arifin & Darmawan (2022) and Karlinda et al, (2022) which state that organizational support will improve employee performance. Based on this description, the hypothesis proposed is: H1: Organizational support has a positive and significant effect on employee performance.…”
Section: Literature Review the Effect Of Organizational Support On Em...mentioning
confidence: 94%
See 1 more Smart Citation
“…Penelitian yang dilakukan oleh (Jufrizen & Hamdani, 2023) menunjukkan adanya penerapan keadilan distributive dan keadilan procedural yang baik maka akan meningkatkan kinerja dari pegawai. (Karlinda et al, 2022) dalam penelitiannya menjelaskan bahwa keadilan organisasi dapat diterapkan dengan peningkatan kewajaran alokasi sumber daya, proses pengambilan keputusan, pemeliharaan hubungan antar pribadi dapat menciptakan lingkungan yang adil bagi setiap pegawai sehingga membuat pegawai lain merasa puas dan rela dalam menyelesaikan pekerjaannya dengan baik. Oleh karena itu, Aturan-aturan tersebut memiliki implikasi yang sangat penting karena dipandang sebagai manifestasi nilai-nilai proses dasar dalam organisasi.…”
Section: Pendahuluanunclassified
“…Semua itu merupakan sebab menurunya kinerja karyawan dalam bekerja. Faktor-faktor yang dapat digunakan untuk meningkatkan kinerja diantaranya adalah gaya kepemimpinan, motivasi dan disiplin kerja [4].…”
Section: E Kemandirianunclassified